Quantum bits with Josephson junctions (Review Article) - Wendin, G.; Shumeiko, V.S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
Recent demonstrations of macroscopic quantum coherence in Josephson junction based electronic circuits opened entirely new dimension for the research and applications in the established field of Josephson electronics. In this article we discuss basic Josephson circuits for qubit applications, methods of quantum description of these circuits, circuit solutions for qubit couplings. Principles of manipulation and readout of superconducting qubits are reviewed and illustrated with recent experiments with various qubit types.